Parameter sensitivity of metal forming processes - Antunez, Horacio Javier; Kleiber, Michal (Computer Assisted Methods in Engineering and Science, 2023)
The flow formulation for metal forming analysis based on a rigid-viscoplastic material model is considered. Specifically, sensitivity evaluation techniques are discussed for different solution variables with respect to variations in parameters entering the constitutive (and other) equations such as material constants, imposed velocities or friction coefficient. A method to avoid spurious pressure modes is introduced which allows to use Ql/Ql elements and thus to accurately calculate pressures, their sensitivities and friction forces. In addition, one pressure unknown for each node is available in this method, thus yielding a finer discretisation for this variable.